THE EFFECT OF ORGANIZATIONAL MANAGEMENT, ACCESSIBILITY, AND NURSES' PROFESSIONALISM ON OUTPATIENT PATIENT SATISFACTION AT THE POLYCLINIC OF DR. R. HARDJANTO HOSPITAL, BALIKPAPAN - Vip Paramarta; Ayu Laili Rahmiyati; Ramadani (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
Patient satisfaction is a key indicator in assessing the quality of hospital services, particularly in outpatient services, which are the starting point for patient interaction with healthcare institutions. Dr. R. Hardjanto Balikpapan Level II Hospital experienced a decline in patient satisfaction by 8.4% and the number of polyclinic visits by 2.54%. This study aims to determine the effect of organizational management, accessibility, and nurse professionalism on outpatient satisfaction. The research method used is quantitative with a survey approach. Data collection was carried out by distributing questionnaires to outpatients, then analyzed using multiple linear regression. The results of the study indicate that partially and simultaneously, organizational management, accessibility, and nurse professionalism have a significant effect on patient satisfaction. Structured organizational management, easy access to services, and professional behavior of nurses have been proven to be able to increase positive patient perceptions of service quality. These findings confirm that these three factors are important components in forming a satisfying service experience in hospitals.